Latin influence in early Malay grammars - Karim Harun, (Fakulti Sains Sosial dan Kemanusiaan, 2009)
The writing of Malay grammar began in the 17th century. The first Malay grammar appeared in the form of a table written by Frederick de Houtman (1603). This was followed by discussion of a few aspects of grammar by Sebastian Danckaerts (1623). And finally with a complete grammar, which was written in 1653 by Joannes Roman. These were the earliest grammars in Malay and also among the earliest in the world. These grammars were influenced much by Latin, in term of conjugations, word classes, etc. In light of this influence, this paper attempts to discuss these grammars from the perspective of history of linguistics. The discussion will focus on the influence of Latin in these grammars. As Latin was a lingua academica at that time, the influence could not be avoided. Thus, this makes Malay a language at par with other languages in the world, especially Latin because Latin means grammar.